ANALISIS VISUAL SPLASH ART KARAKTER LUX PADA GAME “LEAGUE OF LEGENDS” - Josslyn Amelie; Elda Franzia Jasjfi (Jurnal Dimensi DKV Seni Rupa dan Desain, 2023)
The Visual Analysis of Lux Character’s Splash Art on the Game of “League of Legends”. Splash art is a definition that is mostly used in most video games to show the visualization of a playable character in the game. Besides splash art having interesting illustrations, splash art often shows the character's lore to the players, so the player is interested and manifested to play the character or to use the skin on the character. The use of composition is one of the biggest factors that affect the choice to tell the character’s story within its splash art. One of the video games that have splash art that interests most gamers is “League of Legends”. The game“League of Legends” has so many players and invested fans because of the interesting gameplay and the illustration of the character’s splash art. In this journal, one of the characters whose splash art will be explained in analytic matter is Lux. Lux is one of the woman warriors in the “League of Legends” and is known to be very popular. The method is qualitative visual analysis. Visual illustration data collected dan analyzed based on visual design theory, especially commposition, illustration, and colour. The result is that Lux has so many skins variations that can be used in the game and every splash art within the character has a correlation with the character’s lore.Keywords: splash art, game, League of Legends, Lux